Flow control random access protocol for event-driven machine-to-machine traffics in LTE network - Liu YANG; Ping-zhi FAN; Li HAO (Tongxin xuebao)
A flow control random access protocol for event-driven machine-to-machine traffics in LTE network is pro-posed.The beta distribution is adopted to model the event-driven M2M traffics.This protocol uses the random access preamble free ratio in a fixed number of slots to estimate the channel load and calculate the flow control factor to control the flow.The throughput performance of the proposed protocol is modeled and analyzed,and compared with the random access protocol in LTE system.It is shown that the proposed protocol performs much better because it can estimate the system load accurately in most situations and reduce collision by flow control factor.